Relevance of Adherence Monitoring in Adult Patients With Growth Hormone Deficiency Under Replacement Therapy: Preliminary Monocentric Data With EasypodTM Connect - Mancini, Antonio; Vergani, Edoardo; Bruno, Carmine; Palladino, Andrea; Brunetti, Alessandro (Frontiers in Endocrinology, 2019)
Purpose: Non-compliance to recombinant human growth hormone (r-hGH) therapy in adult growth hormone deficiency (aGHD) is a major concern for endocrinologist, as it affects significantly efficacy outcomes. This 12-month observational study was aimed to assess adherence in GHD patients treated with r-hGH administered via EasypodTM, an electronic, fully automated injection device designed to track the time, date and dose administered. Methods: 65 patients receiving r-hGH therapy were included in the study and 32 completed the study. The primary endpoint, adherence to treatment, was calculated as the proportion of injections correctly administered during the observational period out of the expected total number of injections. Adherence, tracked by the EasypodTM, was evaluated at months 6 (V1) and 12 (V2) after baseline (V0). As secondary end-point, serum IGF-1 levels were also determined. Results: The EasypodTM data showed a median adherence of 80% throughout the period V0-V2. Females are more compliant than males. Adherence levels are correlated to IGF-1 ones. Conclusions: Adherence is connected with therapy efficacy in aGHD. The injection-recording system and other characteristics of EasypodTM could enhance the ability of physicians to monitor adherence to r-hGH treatment, identifying non-compliant patients, thus enabling physicians to modify their management to maximize the benefits of the treatment.